Coevolution of cells and viruses in a persistent infection of foot-and-mouth disease virus in cell culture. - de la Torre, J C (1988)
Virus and cells evolve during serial passage of cloned BHK-21 cells persistently infected with foot-and-mouth disease virus (FMDV). These carrier cells, termed C1-BHK-Rc1 (J.C. de la Torre, M. Dávila, F. Sobrino, J. Ortín, and E. Domingo, Virology 145:24-35, 1985), become constitutively resistant to the parental FMDV C-S8c1. Curing of late-passage C1-BHK-Rc1 cells of FMDV by ribavirin treatment (J.C. de la Torre, B. Alarcón, E. Martínez-Salas, L. Carrasco, and E. Domingo, J. Virol. 61:233-235, 1987) did not restore sensitivity to FMDV C-S8c1. The resistance of C1-BHK-Rc1 cells to FMDV C-S8c1 was not due to an impairment of attachment, penetration, or uncoating of the particles but to some intracellular block that resulted in a 100-fold decrease in the amount of FMDV RNA in the infected cells. FMDV R59, the virus isolated from late-passage carrier cells, partly overcame the cellular block and was more cytolytic than FMDV C-S8c1 for BHK-21 cells. Sequencing of the VP1 gene from nine viral clones from C1-BHK-Rc1 cells showed genetic heterogeneity of 5 X 10(-4) substitutions per nucleotide. Mutations were sequentially fixed during persistence. In addition to resistance to FMDV C-S8c1, C1-BHK-Rc1 cells showed a characteristic round cell morphology, and compared with BHK-21 cells, they grew faster in liquid culture, were less subject to contact inhibition of growth, and had an increased ability to form colonies in semisolid agar. Reconstitution of a persistent infection was readily attained with late-passage C1-BHK-Rc1 cells and FMDV C-S8c1 or FMDV R59. The results suggest that coevolution of BHK-21 cells and FMDV contributes to the maintenance of persistence in cell culture.